2002
DOI: 10.2172/805803
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Testing of Carbon Steel in Acid Cleaning Solutions

Abstract: Executive SummaryHigh level waste is stored in carbon steel tanks at the Savannah River Site (SRS). The site is currently in the process of waste removal from, and ultimately closure of, these tanks. One of the most time consuming steps in the waste removal process is cleaning the sludge heel from the bottom of the tanks to an acceptable residual quantity. The sludge consists primarily of metal oxides that formed after waste from the canyons was neutralized with sodium hydroxide. Since the canyon waste was ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…For each scenario, it is commonly assumed that the steel in the engineered barriers (including rebar) for disposed waste or the carbon-steel tank liners holding the liquid waste do not sorb the radionuclides. Tank liners have been shown to form corrosion products, such as FHOs [21]. It is important to understand how extensively radionuclides sorb to corrosion products and if the current risk calculation assumptions are conservative.…”
Section: Introductionmentioning
confidence: 99%
“…For each scenario, it is commonly assumed that the steel in the engineered barriers (including rebar) for disposed waste or the carbon-steel tank liners holding the liquid waste do not sorb the radionuclides. Tank liners have been shown to form corrosion products, such as FHOs [21]. It is important to understand how extensively radionuclides sorb to corrosion products and if the current risk calculation assumptions are conservative.…”
Section: Introductionmentioning
confidence: 99%
“…This amount of corrosion does not significantly impact the structural integrity of the tank (McKeel, 2008) or the performance assessment analysis (Garcia-Diaz, 2010). Previous testing in oxalic/nitric acid mixtures suggested that the corrosion rate for carbon steel in dilute acid mixtures (i.e., 0.3 M nitric acid) would result in a "manageable" amount of degradation over a short period of time (Wiersma, 2002). These expectations were confirmed during recent corrosion evaluations performed in support of the EM-31 chemical cleaning program (Wiersma, 2010).…”
Section: Background and Introductionmentioning
confidence: 71%
“…76 Experimental data for the corrosion of carbon steel in nitric acid at room temperature is shown in Table 27. 77,78,79…”
Section: Nitric Acidmentioning
confidence: 99%
“…Coupon testing of carbon steel was performed in solutions of nitric acid and oxalic acid. 79 Most of the testing was conducted for 3 days at ambient temperature. The general corrosion rates on carbon steel similar to that utilized for the waste tanks are shown in Table 28.…”
Section: Nitric Acid and Oxalic Acidmentioning
confidence: 99%